-5x+2y=6
2y=6+5x
y=5/2x + 6
x+3y=3
3y=3-x
y=-x/3+1
-2x+y=4
y=2x+4
4x+9y=-9
9y=-4x-9
y=-4/9x+1
Hope this helps.
2(4z-3-21)=166-46
Combine like terms
2(4z-24)= 120
Distribute
8z-48= 120
Add 48 to both sides
8z= 168
Divide both sides by 8
z=21
Final answer: z=21
Answer:
$0.74
Step-by-step explanation:
2.22 divided by 3 equals 0.74.
Answer:
y=2x-4
Step-by-step explanation:
y-y1=m(x-x1)
y-10=2(x-7)
y-10=2x-14
y=2x-14+10
y=2x-4
Answer:A2 - b 2=(a + b) ( a - b) where a =2 and b =x2.
2(2 + x2) ( 2 - x2)
Step-by-step explanation:
Since both terms are perfect squares, factor using the difference of squares formula,